Understanding gravitationally induced decoherence parameters in neutrino oscillations using a microscopic quantum mechanical model - Domi, Alba; Eberl, Thomas; Fahn, Max Joseph; Giesel, Kristina; Hennig, Lukas; Katz, Uli; Kemper, Roman; Kobler, Michael (Journal of Cosmology and Astroparticle Physics, 2024)
In this work, a microscopic quantum mechanical model for gravitationally induced decoherence introduced by Blencowe and Xu is investigated in the context of neutrino oscillations. The focus is on the comparison with existing phenomenological models and the physical interpretation of the decoherence parameters in such models. The results show that for neutrino oscillations in vacuum gravitationally induced decoherence can be matched with phenomenological models with decoherence parameters of the form Γij ∼ Δ m 4ij E -2. When matter effects are included, the decoherence parameters exhibit a dependence on the varying matter density across the Earth layers. This behavior can be explained by the nature of the coupling between neutrinos and the gravitational wave environment, as suggested by linearised gravity. On a theoretical level, these different models can be characterised by a different choice of Lindblad operators, with the model with decoherence parameters that do not include matter effects being less suitable from the point of view of linearised gravity. Consequently, in the case of neutrino oscillations in matter, the microscopic model does not agree with many existing phenomenological models that assume constant decoherence parameters in matter. Nonetheless, we identify the KamLAND experimental setup as particularly well-suited to establish the first experimental constraints on the model parameters, namely the neutrino coupling to the gravitational wave environment and its temperature, based on a prior analysis using the phenomenological model.
CRIS-Team Scopus Importer:2024-11-22
Keywords: gravity; neutrino experiments; neutrino theory; solar and atmospheric neutrinos